Coursenotes_ECON301

# 164 1 a contract curve yields allocations xa xb ya yb

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: URE EXCHANGE ECONOMY EXAMPLE Consider a simple pure exchange economy with two consumers, A and B, and two goods, X and Y. Consumer A has a square root utility function while Consumer B has a CobbDouglas utility function with = 0.25, = 0.75, and = 1. There is one unit of each good allocated between the two consumers according to the following endowment distribution: Consumer A Consumer B Total GOOD X XA = XB = X = + = 1 GOOD Y YA = YB = Y = + = 1 We solve this particular pure exchange economy as follows: Let's start with Consumer A. This consumer has a utility function that allows us to determine their marginal rate of substitution and an endowment income that constrains their utility as follows: UA = UA(XA,YA) = X1/2Y1/2 MA = PX XA + PY YA = PX + PY We can figure out consumer A's marginal rate of substitution as: MRSA = MUXA MUYA = 0.5 X-1/2Y1/2 0.5 X1/2Y-1/2 = YA XA At the consumer equilibrium, the two equations consumer A needs to satisfy are: MRSA = YA = PX XA PY PX XA + PY YA = MA 166 (1) (2) Rearranging (1) we get: XA PX = YA PY (3) Meaning we can get demands for XA and YA by subbing (3) into (2) as follows: PX XA + PX XA = MA 2 PX XA = MA XA = M A 2 PX (4) and we know that MA = PX + PY is the endowment income of consumer A, so we sub this in for the MA in (4) to get: XA = PX + PY 2 PX XA = 1/8 + _3PY__ 8 PX PY YA + PY YA = MA 2 PY YA = MA YA = M A 2 PY (6) (5) and we know that MA = PX + PY is the endowment income of consumer A, so we sub this in for the MA in (6) to get: YA = PX + PY 2 PY YA = 3/8 + _PX__ 8 PY (7) Now let's turn our attention to Consumer B. This consumer has a utility function that allows us to determine their marginal rate of substitution and an endowment income that constrains their utility as follows: UB = UB(XB,YB) = X1/4Y3/4 167 MB = PX XB + PY YB = PX + PY We can figure out consumer B's marginal rate of substitution as: MRSB = MUXB MUYB = 0.25 X-3/4Y3/4 0.75 X1/4Y-1/4 = YB 3XB At the consumer equilibrium, the two equations consumer B needs to satisfy are: MRSB = YB = PX 3XB PY Rearranging (1B) we get: PX XB + PY YB = MB 3 XB PX = YB PY (1B) (2B) (3B) Meaning we can get demands for XB and YB by subbing (3B) into (2B) as follows: PX XB + 3 PX XB = MB 4 PX XB = MB XB = MB 4 PX (4B) and we know that MB = PX + PY is the en...
View Full Document

Ask a homework question - tutors are online